Prilagodljiv šolski prostor – ustvarjalno učenje - Filipič Gorenšek, Polona (Šport (Ljubljana), 2022)
Humans have been changing the space of learning since we existed. Indeed, the developmental dynamics that society mirrors through the process of education have always been important for building optimism for a better tomorrow. The result of any quality education system is creative individuals. "The architecture of kindergartens and schools is considered to be one of the most demanding areas of planning, and therefore mere knowledge of norms is often insufficient or even inadequate for the conception and design of such spaces." (Playful Architecture for Schools, 2022) The process of holistic renewal of the education system is therefore not generalisable, but can only be the result of very concrete ideas and actions that take place in close collaboration between the educational and architectural professions. Reforming the education system means introducing innovations both in the field of pedagogy and in the architecture of school buildings. Modern approaches to the design of learning spaces, with a high degree of flexibility, multifunctionality and established interconnections, build on the multiplicity of spatial experiences. In this sense, the school space encourages creativity, which is often linked to the concept of self-fulfilment and progress of the individual and society. As we in our country have not yet seen a change in this direction to any significant extent, this paper examines the state of the art and the possibilities of introducing modern concepts of flexible and adaptable school space in dialogue with new approaches in education. How the physical structure of the building determines or facilitates the activities and forms of the pedagogical process and how the concepts of contemporary pedagogy can influence the change of the school space in the future.
Keywords: arhitektura; gibanje; pedagogika; prilagodljivost; prožnost; šole; šoprt; športna vzgoja